O ASILO E A LOUCURA COMO REPRESENTAÇÕES EM BATMAN: ASILO ARKHAM E O SÉRIO MUNDO DE GRANT MORRISON - Rachelle, Felipe Raul (2019)
This paper consists of analyzing Grant Morrison's graphic novel "Arkham Asylum - A Serious Home in a Serious Earth", released in 1989 by DC Comics in the United States. The work became a reference in the universe of comics, working with themes such as madness, enclosure and dialogue with several elements of classical art. The proposal here is to think the comic as a source, a product of a certain historical period dialoguing with this temporality, working with his technical aspects, the construction of comics as a movement and its history, and the relevance of the authors in these processes, also thinking about the author of the work, Grant Morrison, more specifically, and how he builds his work in order to mark the comic in the artistic and intellectual field. Moreover, this work also dialogues with the materiality of the comic, making an analysis of it and its stylistic and aesthetic resources, and also with the temporality in which the comic was produced and with which it directly dialogues, thinking about the deinstitutionalization of madness, the advancement of debates on psychiatry and antipsychiatry, and how madness has become each once again a fold of the discourse of modern rationality, thinking about how the composition of the characters reflects the debate about madness, and how the author points out that madness is on the same axis as reason, questioning the duality hitherto established.